1993
DOI: 10.1093/oxfordjournals.jbchem.a124088
|View full text |Cite
|
Sign up to set email alerts
|

Requirements of Different Subdomains of Calpastain for Calpain Inhibition and for Binding to Calmodulin-Like Domains1

Abstract: Calpain requires Ca2+ for both proteolysis of its substrates and interaction with its endogenous inhibitor, calpastatin. The mechanism of inhibition of calpain by calpastatin has remained unsolved, although Nishimura and Goll [J. Biol. Chem. 266, 11842-11850 (1991)] reported that autolyzed calpain fragments containing calmodulin-like domains (CaMLDs) bound to an immobilized calpastatin column. We investigated the correlation between CaMLD-binding and calpain inhibition using immobilized columns of gene-enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The above feature conforms to a basic amphiphilic c~-helical motif where hydrophobic and basic residues are localized on each side of the helical cylinder [25]. Likewise, although calpastatin shows little secondary structure in solution [10], the potential c~-helix regions found in the conserved sequences of regions A and C [8,20] may form amphiphilic c~-helical structures upon complexing with the CaMLDs. Indeed, the calpastatin domain 1 mutant, which had a substitution of one of the conserved hydrophobic Leu residues in region A with a helix breaker residue Pro, demonstrated a striking decrease in the binding ability of the L-CaMLD, and also showed reduced calpain inhibition activity [23].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The above feature conforms to a basic amphiphilic c~-helical motif where hydrophobic and basic residues are localized on each side of the helical cylinder [25]. Likewise, although calpastatin shows little secondary structure in solution [10], the potential c~-helix regions found in the conserved sequences of regions A and C [8,20] may form amphiphilic c~-helical structures upon complexing with the CaMLDs. Indeed, the calpastatin domain 1 mutant, which had a substitution of one of the conserved hydrophobic Leu residues in region A with a helix breaker residue Pro, demonstrated a striking decrease in the binding ability of the L-CaMLD, and also showed reduced calpain inhibition activity [23].…”
Section: Resultsmentioning
confidence: 98%
“…The highly conserved internal repeat regions A, B and C are located on separate exons in the human calpastatin gene, suggesting distinct roles in inhibitory function [11,22]. Moreover, regions A and C have similar sequences [6,20]. Recently we showed that the L-CaMLD of/.t-calpain bound in a Ca2+-dependent fashion to calpastatin domain 1 but not to the region B oligopeptide, by using a Sepharose column immobilizing the L-CaMLD fused with glutathione-S-transferase [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some candidate genes like calpain (CAPN4), calpastatin (CAST), diacylglycerol acyltransferase 1 (DGAT1) and fatty acid binding protein 3 (FABP3) have been implicated in muscle development and fat metabolism (Goll et al 1992;Calvo et al 2004;Scata et al 2009). The CAPN4 is a cytosolic endopeptidase that requires calcium for catalytic activity, whereas CAST is a specific endogenous inhibitor that acts on calpain (Ma et al 1993). These genes are involved in muscle development, growth (Nonneman and Koohmaraie, 1999) as well as in eating quality (tenderness) of the mutton (Byun et al 2009).…”
Section: Introductionmentioning
confidence: 99%